2022
DOI: 10.46729/ijstm.v3i5.633
|View full text |Cite
|
Sign up to set email alerts
|

Effect Of Product Quality And Service On Customer Loyalty With Customer Satisfaction As An Intervening Variable (Study On Coffee Shop In Medan)

Abstract: This study is to determine the effect of product quality on consumer loyalty, to determine the quality of service to consumer loyalty. To know the effect of product quality and service quality on customer satisfaction. The type of research used is a type of quantitative research. In this study used 105 sample. Data collection techniques used by researchers in conducting this study is to use an online questionnaire. Data analysis technique of this study is SEM-PLS. From this study it was found that the influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
3
0
1
Order By: Relevance
“…This is in line with the previous study to determine the effect of product quality on consumer loyalty, to determine the quality of service to consumer loyalty. To know the effect of product quality and service quality on customer satisfaction (Tirtayasa, 2022). From this study it was found that the influence of product quality on customer satisfaction is a positive effect and not significant.…”
Section: Discussionmentioning
confidence: 85%
“…This is in line with the previous study to determine the effect of product quality on consumer loyalty, to determine the quality of service to consumer loyalty. To know the effect of product quality and service quality on customer satisfaction (Tirtayasa, 2022). From this study it was found that the influence of product quality on customer satisfaction is a positive effect and not significant.…”
Section: Discussionmentioning
confidence: 85%
“…Nilai t-statistik sebesar 2,527 dan p-value sebesar 0,012 menunjukkan bahwa pengaruh variabel kepuasan pelanggan terhadap loyalitas konsumen lebih besar dari nilai yang diberikan oleh t tabel sebesar 1,96. Hasilnya, kita dapat menyimpulkan bahwa kepuasan pelanggan mempunyai pengaruh positif dan besar terhadap loyalitas konsumen.. Temuan ini konsisten dengan hasil studi sebelumnya yang dilakukan oleh Uddin, (2019), Ing et al, (2020), Mustofa et al, (2017), Andri et al, (2022), Tirtayasa, (2022, Elyana & AC, (2023), Agustin dkk., (2023, dan Akmal et al, (2023) yang menunjukkan bahwa "kepuasan konsumen secara positif dan signifikan mempengaruhi tingkat loyalitas konsumen. Kepuasan konsumen dianggap sebagai indikator utama loyalitas konsumen".…”
Section: Pengaruh Kepuasan Konsumen Terhadap Loyalitas Konsumenunclassified
“…This is not in accordance with previous research. However, research by Tirtayasa (Tirtayasa, 2022) states that service quality has a positive and significant influence on customer loyalty. This means that the more a cafe can meet the needs of its customers, the more consumer loyalty to the cafe will increase.…”
Section: Structural Modelmentioning
confidence: 99%